Computer Mediated Collaborative Word Search in Online Tutoring: A Single Case Analysis - Di Yu; Silvia Maggio (Working Papers in Applied Linguistics and TESOL, 2016)
As internet-based remote communication became one of the primary modes for human interaction, particularly when it has been adopted in instructional and educational contexts, researchers have begun exploring various features of the interactions occurring on or mediated by these platforms. Garcia and Jacobs (1999) examined students’ exchanges on a text-based quasi-synchronous discussion program and found that the turn-taking system differs greatly from naturally-occurring face-to-face interactions such as turn-allocation and projection. Computer-mediated collaboration is also another topic that has been extensively addressed (See for example Heath & Luff, 1992; Luff et al, 2003). It has been found that video-mediated interactional environment can impact participants’ interactional conduct and introduce communicative asymmetries (Heath & Luff, 1992). This short paper analyzes one word-search episode between a teacher and a student during a web-based language tutoring session and demonstrates how the sequence is collaboratively conducted and resolved.